2012
DOI: 10.1159/000337325
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Screening for Novel Preeclampsia Biomarker Candidates

Abstract: Introduction: Our aim was to identify novel biomarker candidates for the near-term prediction of preeclampsia in a homogenous collective. In this study, we screened at the genome-wide level for gene expression in placental villous tissue from patients with severe preeclampsia in comparison to normal healthy pregnancies. Material and Methods: Total RNA was extracted from placental villous tissue from 9 preeclamptic patients and 7 normotensive controls after scheduled cesarean sections. After sample pooling, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…Higher methylation was also observed in some genes in the preeclampsia (Jia et al 2012). Here, we showed that the differentially expressed genes in preeclampsia placental tissues were mainly enriched in several pathways associated with pregnancy maintenance, metabolism, oxidative stress and oxidative metabolism, cell cycle regulation, embryogenesis and development, implantation, placentation and decidualization, immune modulation, and vascular function (Zhou et al 2006;Laivuori 2007;Founds et al 2009;Johansson et al 2011;Løset et al 2011;Rajakumar et al 2011;Sado et al 2011;Tsai et al 2011;Jia et al 2012;Lapaire et al 2012). We summarized the major functional categories on the differential gene expression profile between preeclampsia and normal placentas ( Table 1).…”
Section: Preeclampsia Susceptibility Genesmentioning
confidence: 84%
See 2 more Smart Citations
“…Higher methylation was also observed in some genes in the preeclampsia (Jia et al 2012). Here, we showed that the differentially expressed genes in preeclampsia placental tissues were mainly enriched in several pathways associated with pregnancy maintenance, metabolism, oxidative stress and oxidative metabolism, cell cycle regulation, embryogenesis and development, implantation, placentation and decidualization, immune modulation, and vascular function (Zhou et al 2006;Laivuori 2007;Founds et al 2009;Johansson et al 2011;Løset et al 2011;Rajakumar et al 2011;Sado et al 2011;Tsai et al 2011;Jia et al 2012;Lapaire et al 2012). We summarized the major functional categories on the differential gene expression profile between preeclampsia and normal placentas ( Table 1).…”
Section: Preeclampsia Susceptibility Genesmentioning
confidence: 84%
“…This review provides a detailed overview of typical genome-wide studies that have been conducted so far on preeclamptic placental tissue samples (Zhou et al 2006;Laivuori 2007;Founds et al 2009;Johansson et al 2011;Løset et al 2011;Rajakumar et al 2011;Sado et al 2011;Tsai et al 2011;Jia et al 2012;Lapaire et al 2012).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several gene expression studies (Lapaire et al, 2012;Louwen et al, 2012;Meng et al, 2012;Zhou et al, 2013) have been conducted to investigate expression differences between preeclampsia patients and healthy controls. The major challenge for microarray analysis is to develop a suitable statistical model to deal with the small sample number and large number of genes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence has shown that weight and smoking status are risk factors for the pathogenesis of PE [5]. Recently, there has been increasing evidence that free β-human chorionic gonadotropin (β-hCG) is associated with PE [6]. …”
Section: Introductionmentioning
confidence: 99%